A loss of function mutation in SOCS2 results in increased inflammatory response of macrophages to TLR ligands and Staphylococcus aureus - Guzylack-Piriou, Laurence; Gausseres, Blandine; Tasca, Christian; Hassel, Chervin; Tabouret, Guillaume; Foucras, Gilles (Frontiers in Immunology, 2024)
The role of suppressor of cytokine signaling (SOCS)2 in anti-infective bacterial immunity has been poorly investigated compared to other members of the SOCS family. We characterized the previously identified loss of function R96C point mutation of SOCS2 using a genome-edited mouse model that resumes the phenotype of Socs2 knockout mice. The response of macrophages to TLR-ligands and Staphylococcus aureus was examined. Conversely to previously published data using human monocyte-derived macrophages, the stimulation of bone-marrow-derived macrophages with various TLR ligands did not show any difference according to the SOCS2 variant. Upregulation of IL-6 and TNF-α pro-inflammatory cytokines production was only seen when the SOCS2 expression was promoted by the culture of macrophages in the presence of GM-CSF. Furthermore, we showed that the SOCS2 point mutation is associated with heightened STAT5 phosphorylation in a short time frame upon GM-CSF incubation. In mice, recruitment of neutrophil and F4/80 int Ly6C + inflammatory macrophage, as well as IFN-γ and IL-10 concentrations, are significantly increased upon S. aureus peritoneal infection. Altogether, these data support the idea that by lowering the pro-inflammatory environment, SOCS2 favors better control of bacterial burden during a systemic infection caused by S. aureus.